2016
DOI: 10.18178/ijesd.2016.7.10.869
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of Methylene Blue and Methyl Orange Using Eichhornia crassipes

Abstract: Abstract-Phytoremediation is defined as the use of plants and their associated microorganisms to remove harmless pollutants from contaminated sites. It is a promising approach in the treatment of dye wastewater due its cost-effectiveness. The aim of this study was to determine the effectiveness of water hyacinth (Eichhornia crassipes) in removing color. Water hyacinth was used to treat 50 mg/L of methylene blue (MB) and 50 mg/L of methyl orange (MO) for 20 days under ambient temperature (30±1 °C). The pH of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 13 publications
0
25
0
1
Order By: Relevance
“…The plant C. roseus able to bear the toxic impact of dyes but the rate of decolourisation is quite slow for both MB and CR dyes. In the preceding work, the removal of MB was also reported through phytoremediation process with the help of aquatic plant Eichhornia crassipes and Lemna minor [40,3]. The researcher reported that E.…”
Section: Resultsmentioning
confidence: 99%
“…The plant C. roseus able to bear the toxic impact of dyes but the rate of decolourisation is quite slow for both MB and CR dyes. In the preceding work, the removal of MB was also reported through phytoremediation process with the help of aquatic plant Eichhornia crassipes and Lemna minor [40,3]. The researcher reported that E.…”
Section: Resultsmentioning
confidence: 99%
“…It can grow up to 20 cm long and the fern colour is light green to medium green colour, with brownish edges when mature 31 . Much research deals with floating plants, which are highly tolerable to many environmental contaminants, such as heavy metals and hydrocarbons 32,33 , but few studies have shown that the plants have the ability to biodecolorize textile dyes 2,34 . In the present study, the aim of this research was to explore the ability of Salvinia molesta to decolourize MO dye in synthetic wastewater.…”
Section: Role Of Salvinia Molesta In Biodecolorization Of Methyl Oranmentioning
confidence: 99%
“…They are ideal plants for phytoremediation because both plants can proliferate to a large extent, and they are known to develop rapidly and in an invasive manner, covering the surface of the water to prevent sunlight from entering the lower layers of water, thereby preventing the spread of photosynthetic plants in the lower layers [13][14][15][16][17]. E. crassipes is considered as the ideal water plant for rhizofiltration of noxious elements and is accepted worldwide in treating wastewaters, being infamous for its fast, uncontrolled growth, its high tolerance to pollutions, and its capability to uptake heavy metals and persistent organic pollutants together with nutrients [14,18,19]. As researchers have shown, Salvinia sp.…”
Section: Introductionmentioning
confidence: 99%